A Internet como tecnointeração da aprendizagem: valorização da cultura e identidade juvenil - Assunção, Zoraia da Silva (2008)
The present study investigates Internet as technological interaction in the school environment as a resource of the teaching-learning process. It aims to discuss the lack of synchronicity between proposals of educational access for Internet use and types of access and interaction applied by youngsters. For the development of this research, I resorted to a qualitative, descriptive and explanatory research focused on a group whose subjects are youngsters from eleven to fifteen years of age in a catholic school which belongs to a group of private teaching schools in Natal city, Rio Grande do Norte state. As methodological option it focus on a group and the observation of its participation, discourse analysis and ethnography, considering facts and data of the pedagogical practice concerning the focused theme, besides the attempt to know the youngsters everyday at school and the relationship between them and juvenile cultures. It recognizes the existence of two moments of the focused group: the first related to internet use like technological interaction; the second concerns to the way Internet is problematic as technological interaction in classroom learning. While contacting with youngsters, the study discusses the concepts of Media Environments, Culture, Identity, Network, Consumption and Citizenship. It recognizes that it is relevant for the school to consider Internet a pedagogical tool, directed not just at research, but mostly as learning environment and as learning construction in a collaborative way. It points out the need of approach between school and media environment, reevaluating the pedagogical practice, offering a new evaluation proposal (self-evaluation). It suggests a renewal in the teacher's pedagogical practice in the classroom and using Internet, valuing the connection between technological interaction and communication as motivation elements of student s learning construction and their effective participation in decisions involving citizenship. It gives priority to educational work directed at the establishment of dialogic relationship between codes, learning and contents, leading to the new findings domain in the media environment, enabling the development of abilities and performances directed at the recognition and consumption of information from a critical reading of the media